Toxic effect of some plant extracts on Phytophthora capsici the foot rot pathogen of black pepper - N.K. LEELA, M. ANANDARAJ and (Indian Phytopathology, 2002)
Aqueous leaf extracts from Azadirachta indica, Chromolaena odorata, Lantana camera, Piper colubrinum and Strychnos nux-vomica were tested against vegetative and reproductive phases of P. capsici. P. colubrinum was resistant to P. capsici. Mycelial growth, sporangial production, zoospore production and release, and zoospore germination were completely inhibited by C. odorata extracts at 2% concn. Similar results occurred with A. indica extracts although mycelial growth was inhibited by 75.5%. P. colubrinum extracts inhibited mycelial growth and sporangial production and sporangial germination and zoospore germination were inhibited by 23.7 and 20.4%, respectively, at 2% concn. S. nux-vomica extracts inhibited sporangial production at 0.25% concn but was not effective against other phases of P. capsici. L. camera extracts were effective at 2% concn. It is concluded that the water soluble toxic extracts of A. indica and C. odorata are ideal for developing into fungicides.